Domestic and International Doctoral Students’ Motivation to Study at Hungarian Universities - Daria Borodina; Adrian Estrela Pereira (GiLE Journal of Skills Development)
Hungary is a member of the European Higher Education Area (EHEA) and follows a three-cycle higher education system based on the Bologna Process. Raising the number of international and domestic PhD students improves the position of Hungarian universities in international competition for higher education. There are around ten thousand full-time doctoral students; nearly 32% are internationals in Hungary, according to the Central Statistical Office. A great number of higher education institutions develop doctoral programs to attract more domestic and international students, hence, it is significantly important to get to know about students’ motivation to enrol in doctoral study in Hungary. This study was conducted in 2023 and examined international and domestic students’ motivation using the two-factor model of intrinsic and extrinsic motivation proposed by the self-determination theory of human motivation. A questionnaire was administered to 100 international doctoral students, 45 males and 55 females, aged 25 to 45, and to 100 domestic doctoral students, 38 males and 62 females, aged 25 to 48 to explore the motivation to attend a Hungarian university. The results of the study show that the respondents endorsed more items on intrinsic motivation than on extrinsic motivation. There is a significant difference in motivation among domestic and international doctoral students at Hungarian universities. Domestic students demonstrate a higher level of motivation to get knowledge and a higher level of introjected regulation. International doctoral students show a higher level of amotivation compared to domestic students. The existing literature on international education is mostly focused on the skills and benefits students gain, but there has been limited research on doctoral students' motivation. At the same time, knowledge about international and domestic doctoral students' motivation can be used in program development which fits more to the motivational characteristics of doctoral students.